2018
DOI: 10.1002/bies.201800077
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences Run Deep: Toxic Early Life Stress, Telomeres, and Mitochondrial DNA Copy Number, the Biological Markers of Cumulative Stress

Abstract: This manuscript reviews recent evidence supporting the utility of telomeres and mitochondrial DNA copy number (mtDNAcn) in detecting the biological impacts of adverse childhood experiences (ACEs) and outlines mechanisms that may mediate the connection between early stress and poor physical and mental health. Critical to interrupting the health sequelae of ACEs such as abuse, neglect, and neighborhood disorder, is the discovery of biomarkers of risk and resilience. The molecular markers of chronic stress exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 125 publications
1
69
2
1
Order By: Relevance
“…All three markers investigated in this study have been shown to be influenced by stress exposure, which may be acting as a mediator in BD's accelerated aging process. Oxidative stress, which is characterized by an imbalance between oxidants and antioxidants in favor of the oxidants, is known to disrupt the redox signaling and control and accelerate aging processes by leading to accumulation of cellular damage .…”
Section: Discussionmentioning
confidence: 89%
“…All three markers investigated in this study have been shown to be influenced by stress exposure, which may be acting as a mediator in BD's accelerated aging process. Oxidative stress, which is characterized by an imbalance between oxidants and antioxidants in favor of the oxidants, is known to disrupt the redox signaling and control and accelerate aging processes by leading to accumulation of cellular damage .…”
Section: Discussionmentioning
confidence: 89%
“…However, one must not get 11 carried away with how this is framed. While, on the one hand there is evidence for 'biological marks of stress' (Ridout et al, 2018), this is quite simply a sign of normal functioning. If we were able to examine all of our molecular and physiological structures, we would find biological marks for many other of our experiences, and some of these would probably affect our health.…”
Section: Adverse Childhood Experiences Emerge In Social Epidemiologymentioning
confidence: 99%
“…Childhood trauma also increases the risk of respiratory, heart, and metabolic diseases [ 13 ]. Childhood trauma deteriorates health through various mechanisms such as systemic inflammation [ 14 ], reducing telomere length [ 15 , 16 , 17 , 18 ], and DNA methylation [ 19 , 20 , 21 ]. Exposure to childhood trauma also impacts the developing brain [ 22 ].…”
Section: Introductionmentioning
confidence: 99%